INDICATORS OXIDATIVE STRESS IN INFLAMMATORY KIDNEY DISEASES OF DIFFERENT ETIOLOGIES - Король, Л.В. (World of Medicine and Biology, 2015)
The comparative study of the markers activity of oxidative stress in inflammatory diseases of the kidneys: in 106 pyelonephritis patients and 61 glomerulonephritis patients without prejudice excretory function of the kidneys. It is established that the development of inflammatory kidney diseases accompanied by activation of the lipids and proteins oxidation. The degree of oxidation depends on the activity of inflammation (acute or chronic) and its etiology. The activity of these processes can produce high due to lack of antioxidant protection (by reducing the depletion of antioxidants and their stocks at prolonged oxidative stress) and activation of immunological reactions involving pro-inflammatory cytokines. This should be considered in the correction of oxidative stress in patients with inflammatory kidney disease.
Keywords: oxidative stress; lipid peroxidation; oxidative modification of proteins; antioxidant protection; inflammatory kidney disease